2015 IEEE 23rd International Conference on Program Comprehension 2015
DOI: 10.1109/icpc.2015.34
|View full text |Cite
|
Sign up to set email alerts
|

The Last Line Effect

Abstract: Abstract-Micro-clones are tiny duplicated pieces of code; they typically comprise only a few statements or lines. In this paper, we expose the "last line effect," the phenomenon that the last line or statement in a micro-clone is much more likely to contain an error than the previous lines or statements. We do this by analyzing 208 open source projects and reporting on 202 faulty micro-clones.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 5 publications
(11 reference statements)
0
1
0
Order By: Relevance
“…Micro-clones are pattern duplications within the same rule. In the case of code clones, an eect has been observed that the last in a set of micro-clones is particularly prone to errors [33]. Internal clones, as exemplied in our running example, extend to multiple rules within the same The reuse mechanisms found in transformation languages [8] correspond to these scopes.…”
Section: Denition 3 (Rule Clone) Given a Setmentioning
confidence: 67%
“…Micro-clones are pattern duplications within the same rule. In the case of code clones, an eect has been observed that the last in a set of micro-clones is particularly prone to errors [33]. Internal clones, as exemplied in our running example, extend to multiple rules within the same The reuse mechanisms found in transformation languages [8] correspond to these scopes.…”
Section: Denition 3 (Rule Clone) Given a Setmentioning
confidence: 67%